2010
DOI: 10.3989/egeol.40133.091
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the alkali-silica reaction (ASR) in granitic aggregates

Abstract: IntroductionStanton studied in 1940 the Parker Davis dam in California, which showed cracking and expansion. As a result of his study, Stanton concluded that the damage was due to an interaction between aggregates (altered andesites and rhyolites) and the alkalis of the concrete pore solution (Poole, 1992).Since Stanton's discovery the knowledge of alkali-aggregate reaction (AAR) has progressed but still

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
1
Order By: Relevance
“…However, although the criterion in LNEC E 461 [20] uses the lowest expansion limits and a shorter test period (twelve weeks), the interpretation of the aggregates' behaviour in RILEM AAR-4.1 shows that this criterion is effective in the detection of almost all the aggregates classified as potentially reactive by the criterion in Lindgård et al [19], which uses a test period of twenty weeks. The potential reactivity detected for aggregates GR3, GR19 and GR20 in RILEM AAR-4.1 can be, probably, justified by the great abundance of microcracks in those aggregates, which was pointed out by Velasco-Torres et al [29] as the main responsible for the interstitial fluid intake to the siliceous components in the aggregates. The assumption in LNEC E 461 [20] that petrographic characterization is not sufficient for the classification of granitic aggregates seems to be justified, since some potentially reactive behaviours that were observed in RILEM AAR-4.1 were not identified by the petrographic characterization.…”
Section: Ramos | I Fernandes | a S Silva | D Soares | F Noronhamentioning
confidence: 79%
“…However, although the criterion in LNEC E 461 [20] uses the lowest expansion limits and a shorter test period (twelve weeks), the interpretation of the aggregates' behaviour in RILEM AAR-4.1 shows that this criterion is effective in the detection of almost all the aggregates classified as potentially reactive by the criterion in Lindgård et al [19], which uses a test period of twenty weeks. The potential reactivity detected for aggregates GR3, GR19 and GR20 in RILEM AAR-4.1 can be, probably, justified by the great abundance of microcracks in those aggregates, which was pointed out by Velasco-Torres et al [29] as the main responsible for the interstitial fluid intake to the siliceous components in the aggregates. The assumption in LNEC E 461 [20] that petrographic characterization is not sufficient for the classification of granitic aggregates seems to be justified, since some potentially reactive behaviours that were observed in RILEM AAR-4.1 were not identified by the petrographic characterization.…”
Section: Ramos | I Fernandes | a S Silva | D Soares | F Noronhamentioning
confidence: 79%
“…Velasco-Torres et al (38) carried out a comparative study of two granitic rocks extracted from two dams affected by alkali-silica reaction, with slow and fast reactions, respectively, classifying the reactivity of the rocks according to their geological term. They concluded that the reaction can be slow or fast for any given type of rock depending on its components and/or its microstructural characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Gogte 1973;Grattan-Bellew 1992;Kerrick and Hooton 1992;Shayan 1993;Wenk et al 2008). However, microcracks in the aggregate particles also provide easy access to quartz grains in the interior, as suggested by Velasco-Torres et al (2010).…”
mentioning
confidence: 99%